Change of Direction Speed Tests in Basketball Players: A Brief Review of Test Varieties and Recent Trends - Sugiyama, Takashi; Maeo, Sumiaki; Kurihara, Toshiyuki; Kanehisa, Hiroaki; Isaka, Tadao (Frontiers in Sports and Active Living, 2021)
Change of direction speed (CODS) is essential for basketball performance, extensively assessed by various tests. This review aimed to summarize the varieties and trends in CODS tests for basketball players on publications until 2019. Electronic literature searches were conducted using three databases with relevant keywords. Seventy-seven studies were found eligible, conducting CODS tests 120 times in total with 41 individual tests (varieties). To explore the trends, each test was categorized into one of three types based on the distinctive movement characteristics and cutting/turning angles as follows: Shuffle (involving lateral movements), 180°-turn (exerting only 180-degree turns), and Multi-directional-cut (cutting multi-directionally). We then counted the number of publications and adopted times reported per year for each test and categorized type, and calculated the adoption rate for each test type at a five-year interval. The first CODS test performed in basketball players was the T-Test, reported in 1991, and this was the most commonly adopted test (30/120 times). The number of publications and test varieties abruptly increased in the last decade. However, the three types of the Shuffle, 180°-turn, and Multi-directional-cut had similar adoption rates after 2010, each composing one-third of their sum. These findings suggest that while CODS performances in basketball players are increasingly studied with various tests, recent studies give equal weight to all of the three categorized test types to assess specific CODS performances. This review will provide useful information for strength and conditioning coaches to select appropriate tests for evaluating CODS performances of basketball players.